Angiogenesis of Extracted Tooth Wound on Wistar Rats After Application of Okra (Abelmoschus esculentus) Gel Extract - Muhammad Luthfi; Wisnu Setyari Juliastuti; Yuniar Aliyah Risky (Association of Support to Oral Health Research (APESB), 2022)
Objective: To analyze angiogenesis in the post-extracted tooth of Wistar rats after application of okra (Abelmoschus esculentus) extract. Material and Methods: A total of 18 rats were divided into two groups (control and treatment). Okra extract with a concentration of 30% in gel form was applied on the post- extraction socket of the treatment group. The rats were sacrificed on day-3, day-5, and day-7 after tooth extraction. The newly-formed blood vessels were counted and statistically analyzed by means of One Way ANOVA and Tukey HSD with a significance level set at 5%. Results: The newly-formed capillaries of the control group (4.67 ± 1.53) on day-3 were lower than the treatment group (9.00 ± 1.00). The newly-formed capillaries recorded from the control group, both in day-5 (9.33 ± 1.53) and day-7 (8.67 ± 1.53) were lower than the treatment group, which started to decreased from day-5 (13.67 ± 1.53) to day-7 (12.33 ± 0.58). Significant differences were found in treatment group, on day-3 compared to day-5 (p=0.005), and on day-3 to day-7 (p=0.024). Conclusion: Okra extract in gel form at 30% concentration can increase the angiogenesis during the wound healing process of the extracted tooth on Wistar rats.